2000
DOI: 10.1038/sj.jhh.1001095
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in women

Abstract: Hypertension in women has received less attention than hypertension in men, and the major controlled trials of antihypertensive therapy have been carried out in populations made up predominantly of and have emphasised outcomes in men. Recently it has been recognised that women develop high blood pressure, particularly systolic hypertension, at an increased rate as they age, and that this age-related blood pressure increase is exaggerated by the menopause. The age-related rise in blood pressure, particularly sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1
11

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 79 publications
3
46
1
11
Order By: Relevance
“…The influence of menopause on BP is difficult to evaluate because menopause coincides with aging [30]. Some studies have reported a strong association between BP and menopause, but other studies have not [30,31]. We found that mean SBP and DBP did not differ significantly between pre-and postmenopausal women after adjusting for age.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…The influence of menopause on BP is difficult to evaluate because menopause coincides with aging [30]. Some studies have reported a strong association between BP and menopause, but other studies have not [30,31]. We found that mean SBP and DBP did not differ significantly between pre-and postmenopausal women after adjusting for age.…”
Section: Discussionsupporting
confidence: 41%
“…In the present study we failed to detect an association between anthropometric measurements including BMI and WC and menopause result similar to that found in other studies [12,26,29]. The influence of menopause on BP is difficult to evaluate because menopause coincides with aging [30]. Some studies have reported a strong association between BP and menopause, but other studies have not [30,31].…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Post-menopausal women have a higher prevalence of hypertension than pre-menopausal women [10][11][12], and are consequently at an increased risk of cardiovascular disease. High blood pressure is a modifiable risk factor, as reductions can lower the incidence of stroke and coronary heart disease (CHD).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, most studies of synthetic progestins for contraception or hormone therapy have revealed a BP-elevating effect. Oral contraceptives in particular appear to precipitate or accelerate hypertension (Rosenthal et al, 2000).…”
Section: Progestin Effects On Blood Pressurementioning
confidence: 99%